PROGRAM PELATIHAN KETERAMPILAN DAN KEWIRAUSAHAAN PADA PASAR JOHAR SELATAN - Radita Diva Lestari; Ardhita Vania Byakta; Chanesya Athifa Zahra; Silfana Chikita (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
South Johar Market in Semarang, Central Java, has great potential for the development of MSMEs, but still needs to be improved in terms of product variety and marketing strategies. The aim of this community service is to empower traders through skills and entrepreneurship training, so that they can optimize their business potential and increase market competitiveness. The methods used include identifying needs through situation analysis, planning mentoring and training activities, as well as collaboration with market managers and the SME development community. The results of the service showed a significant increase in the participants' skills and knowledge. Traders are able to utilize social media for product promotion, increase creativity in product development, and acquire new skills that are relevant to market needs. This program not only increases the empowerment and competitiveness of MSMEs in South Johar Market, but also contributes to local economic growth. Thus, this training program has succeeded in achieving its goal of supporting the development of MSMEs in the South Johar Market, so that this market can become more competitive and widely known.